Market Risk Analysis in Investment Portfolios in Uganda - Mukasa, James (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to examine the market risk analysis in investment portfolios in Uganda. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The study on Market Risk Analysis in Investment Portfolios in Uganda examines factors affecting investors' performance and profitability in the country. It finds significant untapped potential for foreign direct investment (FDI) in Uganda, particularly in the services sector, but also identifies risks like volatile weather, political instability, weak governance, and high inflation. To attract more investors, the study recommends improving regulations, diversifying exports, enhancing regional integration, and promoting tourism. These steps could help Uganda harness its economic potential. Unique Contribution to Theory, Practice and Policy: Modern Portfolio Theory (MPT), Capital Asset Pricing Model (CAPM) & Behavioral Finance Theory may be used to anchor future studies on the examining market risk analysis in investment portfolios in Uganda. Encourage investors to diversify their portfolios across various asset classes and geographic regions to mitigate market risk. Collaborate with regulatory authorities to establish and enforce robust risk management and reporting standards for financial institutions and investment firms operating in Uganda.